HUKUM PERDATA INTERNASIONAL INDONESIA BIDANG HUKUM KELUARGA (FAMILY LAW) DALAM MENJAWAB KEBUTUHAN GLOBAL - Derita Prapti Rahayu (Fakultas Hukum Universitas Bangka Belitung, 2018)
In the current era of globalization and internationalization where economic, social and cultural developments have caused international relations to be infinite which can lead to civil disputes which give rise to the meeting of legal systems of countries in the world that have their own characteristics related to International Private Law. Hopefully there will not be many problems that arise if disputes over different citizenship civilizations are resolved through Alternative dispute resolution. Although when the Al forum decision on alternative dispute resolution was not carried out voluntarily by the parties affected by the execution, the execution of such decisions became the competence of the district court. Especially if the arbitration forum ruling was dropped outside Indonesia, then when the decision is to obtain recognition and execution within the jurisdiction of the Republic of Indonesia, the decision must first obtain an exequature from the Chair of the Central Jakarta District. Court. But the situation will be different if the dispute is not resolved through Alternative dispute resolution but is left to the court authorities to resolve it, it will be different.